Prevalence of multiple sclerosis in Rochdale. Issue 4 (October 1996) - Shepherd, D I; Summers, A
Abstract : The prevalence of multiple sclerosis in the Rochdale Metropolitan Borough in the north east of Greater Manchester has been established. Case ascertainment was partly prospective via a neurological register from 1979 and by contact with general practitioners, therapists, and social services. On prevalence day, 1 January 1989, 254 patients with multiple sclerosis were living in Rochdale. The overall prevalence was 122/100, 000 population and 96/100, 000 population for probable cases only. The peak rate for women aged 35 to 44 years was 437/100, 000 population and for men aged 45 to 54 years 221/100, 000. Familial multiple sclerosis was present in 10.8% of families. In this, the first study in north west England, the prevalence of multiple sclerosis in Rochdale is similar to that in southern England and Wales but lower than that in Scotland.